2012
DOI: 10.1152/ajpheart.00824.2011
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and quantification of whole rat heart laminar structure using high-spatial resolution contrast-enhanced MRI

Abstract: . Visualization and quantification of whole rat heart laminar structure using highspatial resolution contrast-enhanced MRI. Am J Physiol Heart Circ Physiol 302: H287-H298, 2012. First published October 21, 2011; doi:10.1152/ajpheart.00824.2011.-It has been shown by histology that cardiac myocytes are organized into laminae and this structure is important in function, both influencing the spread of electrical activation and enabling myocardial thickening in systole by laminar sliding. We have carried out high-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
98
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 31 publications
5
98
0
Order By: Relevance
“…These layers form a branching network, and they have been referred to as sheets, 45 myolaminae, 10 and, more recently, sheetlets. 6 The laminar architecture described here has been confirmed with contrast-enhanced high-resolution magnetic resonance imaging 6 and diffusion tensor magnetic resonance imaging. 5 Therefore, ventricular tissue is not uniformly connected transverse to the myofiber direction.…”
Section: Myofiber Architecture and Impulse Propagationsupporting
confidence: 59%
See 2 more Smart Citations
“…These layers form a branching network, and they have been referred to as sheets, 45 myolaminae, 10 and, more recently, sheetlets. 6 The laminar architecture described here has been confirmed with contrast-enhanced high-resolution magnetic resonance imaging 6 and diffusion tensor magnetic resonance imaging. 5 Therefore, ventricular tissue is not uniformly connected transverse to the myofiber direction.…”
Section: Myofiber Architecture and Impulse Propagationsupporting
confidence: 59%
“…At the whole-organ level, the geometry of the heart and the muscular architecture of atria and ventricles can be reconstructed in 3D at tissue-scale resolution using various imaging modalities. [5][6][7] However, it is not possible to measure 3D electric activity in the heart wall with equivalent precision.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method is similar to that previously described [16]. Cardiac geometry, anisotropy and orthotropy were imaged in Fomblin with DT-MRI to acquire a resolution of 100-170 mm, a matrix size of 128 Â 128 Â 128, TE ¼ 15 ms, TR ¼ 500 ms and a b value of 1000 s mm 22 .…”
Section: Methodsmentioning
confidence: 99%
“…From histological [32] and high-resolution MRI studies [33], however, the cardiac myofibers in the midwall region were found to be organized in sheets, separated by cleavage planes that reduce mechanical shear stresses during contraction [19,20]. We shall here model the layered architecture of myocardial tissue by reducing diffusivity along the sheet normal direction in the central part of the myocardial wall in the direction normal to the cleavage plane orientation.…”
mentioning
confidence: 99%